Planned Overreaching and Subsequent Short-term Detraining Enhance Cycle Sprint Performance - Hasegawa, Y.; Ijichi, T.; Kurosawa, Y.; Hamaoka, T.; Goto, K. (International Journal of Sports Medicine, 2015)
We investigated the effect of a training program consisting of planned overreaching and subsequent short-term detraining on sprint performance. 24 physically active men participated in an 18-day sprint-training program. They were divided into 2 groups: the overreaching-detraining (OR-DT) and the control (CON) groups. Subjects in the OR-DT group performed 12 consecutive days of maximal cycle sprint training followed by 6 days of detraining, whereas a rest day was provided after every 2 successive training days for the CON group. Peak power output during maximal pedaling increased significantly after 6 days of detraining in the OR-DT group compared with the baseline (P<0.05), whereas no change was observed in CON group. Intramuscular phosphocreatine concentration increased significantly after 12 days of daily training in the OR-DT group (69.3±45.8% increase vs. baseline, P<0.05), and it was maintained after the detraining period (46.6±33.6% increase vs. baseline, P<0.05). However, no change was observed in CON group. No significant changes in blood variables were observed after the training period except significant reduction of serum cortisol in the CON group. Daily sprint training and subsequent short-term detraining enhanced peak power output after the detraining period.
Keywords: overtraining; rest distribution; phosphocreatine; magnetic resonance spectroscopy; anaerobic power; sprint training